A qualitative study on the impact of local wisdom-based discovery learning in teaching concept geometry - Sayangan, Yohanes Vianey (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Teaching geometric concepts in elementary schools often faces challenges because traditional methods do not activly engage students and fail to utilize local wisdom.Aim: This study aims to assess the impact of applying a local wisdom-based discovery learning model on the understanding of geometric shapes among fifth-grade students.Method: This research employs a descriptive analysis method with a qualitative approach. Data collection was conducted through various means, including observation, interviews, and document analysis. The informants consisted of the school principal, vice principal, teachers, parents, and retired school principals. Data analysis was carried out in a cyclical and interactive manner, involving data collection, data presentation, data reduction, and drawing verification conclusions.Results: The findings indicate that the Discovery Learning model, using local media, successfully stimulates student engagement and creativity, particularly in geometry learning.Conclusion: The use of an appropriate learning model accompanied by local media can be an effective choice in enhancing student involvement and active participation in the learning process. Integrating local wisdom into learning models can be an effective strategy for enhancing the quality of mathematics education in elementary schools. For future research, it is recommended that this study be expanded to include other schools with diverse demographic variations and to compare the impact of this model with other teaching methods.